مدى كفاية أحكام الحماية لحقوق المؤلف للمصنفات المنشورة على شبكة الانترنت في القانون الأردني والاتفاقيات والمعاهدات الدولية - العواملة، عاطف سالم حسين; الأحمد، نضال إبراهيم; العدوان، وضاح سعود (جمعية المكتبات والمعلومات الاردنية, 2014)
Copyright, as well as international conventions and treaties regarding electronically published works, in Jordanian Legislation, had been honored with protection and regulation, especially on the Internet, to ensure the idea of fair dealing, but what impaired Jordanian Law of Copyright, in 1992, was the lack of awareness of all challenges that face authors' copyrights, regarding their published works on the Internet, which caused loss and missing of copyrights, Materially and morally; this requires comprehensive review of all legal texts, domestically and internationally, to accommodate all ways and forms of Infringement of intellectual property rights, at present and in the future, and adoption of applied mechanism capable of protecting copyrights of works published on the Internet.
حظيت حقوق المؤلف في التشريع الأردني والاتفاقيات والمعاهدات الدولية للمصنفات المنشورة إلكترونياً وخصوصاً على الإنترنت، باهتمام الحماية والتنظيم لتأمين فكرة التعامل العادل، إلا أن ما شاب القانون الأردني لحق المؤلف لسنة 1992، والاتفاقيات والمعاهدات الدولية لحماية حقوق المؤلف من قصور في الإحاطة بكافة التحديات التي تواجه حقوق المؤلف لمصنفاته المنشورة على الانترنت، أدى إلى إهدار وضياع حقوق المؤلف من مادية وأدبية، الأمر الذي يوجب إجراء مراجعة شاملة لكافة النصوص القانونية محلياً ودولياً لاستيعاب جميع صور وأشكال الاعتداءات الحالية والمستقبلية، وإقرار آليات تطبيقيه قادرة على حماية حقوق المؤلف للمصنفات المنشورة على الإنترنت.
Keywords: الاتفاقيات الدولية -- حقوق المؤلف -- النشر الالكتروني -- الانترنت -- القوانين والتشريعات -- الأردن -- الحماية القانونية